Artificial intelligence and employee outcomes: Investigating the role of job insecurity and technostress in the hospitality industry - Muhammad Naeem Sharif; Li Zhang; Muhammad Asif; Sajead Mowafaq Alshdaifat; Jalal Rajeh Hanaysha (Acta Psychologica)
Drawing on self-determination theory (SDT), this research examines how the utilization of artificial intelligence (AI) in hospitality organizations is influencing employee work and career outcomes (well-being and career success). We explore the underlying role of job insecurity in the associations of AI use with employee wellbeing and career success. We further explore the boundary condition effect of technostress in our proposed model. This study used a three-wave online survey approach to collect data from 277 workers of fast-food chain restaurants in the People's Republic of China. We used Smart PLS 4 to analyze our data. The results showed a positive relationship among AI use and employee well-being, but not with career success. Job insecurity mediates the relationship between AI use and employee outcomes. Additionally, technostress moderated the associations between AI use and employee well-being and career success. This study contributes to the theory and practice in the field of AI and hospitality industry and helps understand the nexus between increasing use of AI and employees' work and career outcomes.